Nilai Sufistik Tarekat Idrisiyyah dalam Mengembangkan Karakter Santri - Muhamad Abdul Azis; Yulianti Yulianti; Muhtar Gojali (Jurnal Riset Agama, 2021)
This paper purpose is to determine how the concept of the value of Sufism in Idrisiyyah Islamic Boarding School Tasikmalaya. Second, how to apply the values of Sufism of the Idrisiyyah Tarekat in developing the character of the students of the Idrisiyyah Islamic Boarding School Tasikmalaya.this paper used qualitative method which data source from observation, interview, and literatures that related with the topic. The research result shows that Idrisiyyah as a religious institution engaged in an effort to develop the character of the students emphasizes on three religious pillars namely Faith, Islam, Ihsan, in the pattern of Sufism put forward Sufism amali oriented to Tazkiyyah annafsh (cleansing of the soul) tashfiyah al-qalb (building a positive character), and tahdzib al-akhlaq (building akhlakul karimah) trying to instill a positive character for the santri. One of the efforts to handle santri not be deceived by the world is with cultivation of sufistic values guided directly by Mursyid Tarekat Idrisiyyah namely Sheikh Akbar Muhammad Fathurrahman. Dhikr gives meaning to self-awareness which then encourages him consciously and with full responsibility to continue his dynamic life mission of giving meaning through righteous deeds.